THE EVOLUTION OF PLANETARY NEBULAE(PN) AND FADING TIME ACCORDING TO SYNTHETIC MODEL - Abutaib, Muhamed; Ali, Nedera; Abdullah, Sundus (Iraqi Journal of Science, 2024)
Planetary nebulae (PN) represents the short phase in the life of stars with masses(0.89-7) M☉. Several physical processes taking place during the red giant phase oflow and intermediates-mass stars. These processes include :1) The regular (early )wind and the envelope ejection, 2) The thermal pulses during Asymptotic GiantBranch (AGB ) phase. In this paper it is briefly discussed how such processes affectthe mass range of Planetary Nebulae(PN) nuclei(core) and their evolution, and thePN life time, and fading time for the masses which adopted. The Synthetic model isadopted. The envelope mass of star (MeN ) and transition time (ttr) calculatedrespectively for the parameter (MeR =1.5,2, 3×10-3 M☉). Another time scale is ofcapital importance for the understanding of PN and their nuclei, it is the fading time( tf). The results indicated that for each observed nebulae( ttr < tPN) also the fadingtime is sensitive to mass core(MH) of star, the mass with 1.2 M☉ takes only (25 yr )to fading, while the mass with (0.66 M☉) takes about ( 4715 yr) years to fading. Thecalculations showed that (ttr) increases with the increasing of final mass( Mf). Theinitial nebulae radius will also increase with (Mf) thus will correlate with thelocation of nucleus on the HR diagram.